Modeling, Simulation and Implementation of PV Cell/Modules Using PSpice - Messaadi Lotfi; Dibi Zohir (Журнал нано- та електронної фізики)
This paper presents a Spice model of a photovoltaic cell. This model is based on mathematical equations and is described through an equivalent circuit including a photocurrent source, a diode, a series resistor and a shunt resistor. The PSpice is used to simulate a circuit based model for PV cells then to conduct behavioral study under varying conditions of solar insolation including shading effect, temperature, diode model parameters, series and shunt resistance . The study is very helpful in clearly outlining the principles and the intricacies of PV cells and may surely be used to verify impact of different topologies and control techniques on the performance of different types of PV system. In order to validate the developed model, an experimental test bench was built and the obtained results exhibited a good agreement with the simulation ones.